FAMILY HOLIDAYS: TRADITIONS AND CONTEMPORANEITY - Hasba, Astanda Salvovna (History, Archeology and Ethnography of the Caucasus, 2018)
The choice of the research topic is determined by the importance of the family in the aspect of transferring family traditions to the younger generations. Traditions, thanks to the adaptation to modern life, change. However, their significance remains unchanged. They are to serve the strengthening of family-kinship ties and relations, to the transfer of cultural values to succeeding generations. In Abkhazia, family traditions have been honored and protected from the ancient times. The Abkhaz family continues to play an important role in performing various rituals related to various family and calendar events and holidays. One of the main holidays in the cycle of rituals of the traditional ethnic religion of the Abkhazians is - Azhyrnoyu. The Abkhazian holidays were influenced by the intertwining of the beliefs of local residents, and therefore traditionally are celebrated by the Christians: the Christmass, Easter, Assumption of the Blessed Virgin, the Muslim holiday of Kurban-Bayram. Among the preserved holidays of the Soviet period in the Abkhazian tradition there were the celebrations on May 1, May 9 and March 8. Victory Day is a national holiday in Abkhazia. Since May 9, Victory Day in the Great Patriotic War is connected with another holiday of the victory of the Abkhaz people - September 30 became the Independence Day and the Victory Day in the war of 1992-1993. The holidays of Abkhazia brightly and fully convey the diversity and richness of the local culture. Abkhazia, throughout its difficult history, managed to preserve its identity and today defends its interests in an uneasy geopolitical world.